ChemInform Abstract: Challenges in Modelling Homogeneous Catalysis: New Answers from ab initio Molecular Dynamics to the Controversy over the Wacker Process. Issue 37 (16th September 2014) - Stirling, Andras; Nair, Nisanth N.; Lledos, Agusti; Ujaque, Gregori
Abstract Review: 50 refs.